2012
DOI: 10.2522/ptj.20110484
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Functional Outcome at Six Months Following Total Hip Arthroplasty

Abstract: It is possible to identify those patients who are at risk for an unsuccessful outcome through the use of variables such as body mass index, age, and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…This data may have influenced the improvement of the results, since literature emphasizes that THA is a procedure that aims to improve individual's quality of life, therefore it is elective. Corroborating to the findings of this study, similar research showed evidence that BMI is a predictor for THA positive results (Slaven, ) and showed predominant mean age of patients around 59.17 ( SD = 14.7) (Pinto et al., ). Literature suggests as negative factors associated to the postoperative recovery comorbidities, obesity and advanced age (Silva, Santos, Carvalho Júnior, & Matos, ), though this study showed a sample with opposite factors.…”
Section: Discussionsupporting
confidence: 86%
“…This data may have influenced the improvement of the results, since literature emphasizes that THA is a procedure that aims to improve individual's quality of life, therefore it is elective. Corroborating to the findings of this study, similar research showed evidence that BMI is a predictor for THA positive results (Slaven, ) and showed predominant mean age of patients around 59.17 ( SD = 14.7) (Pinto et al., ). Literature suggests as negative factors associated to the postoperative recovery comorbidities, obesity and advanced age (Silva, Santos, Carvalho Júnior, & Matos, ), though this study showed a sample with opposite factors.…”
Section: Discussionsupporting
confidence: 86%
“…Our analysis showed that age and BMI were associated with the TUG test score at all postoperative time points. It is possible to identify patients with THA who are at risk of an unsuccessful outcome by using variables such as BMI, age, and sex [13]. Our findings suggest that age may also be an important predictor of ambulation ability when muscle strength and leg function had almost improved after THA.…”
Section: Discussionmentioning
confidence: 83%
“…Several parameters have been considered as possible preoperative predictors of ambulation outcome after THA in patients with OA. Preoperative factors associated with functional outcome include age, gender, physical function, level of pain, comorbid conditions, Medical Outcomes Study 36-Item Short Form Health Survey (SF-36) score, Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score, and perception of self-efficacy [2, 4, 5, 913]. Based on these studies, we hypothesized that certain preoperative factors would influence changes in ambulation ability at different postoperative time points after THA.…”
Section: Introductionmentioning
confidence: 99%
“…Tests for the statistical significance of time were used to assess the intervention effects. Previous studies showed that age and gender are factors that influence the recovery of patients from THR and their functional outcomes (Nankaku et al, 2013;Singh & Lewallen, 2010;Slaven, 2012). Therefore, age and gender were used as covariates in the GEE analyses.…”
Section: Data Analysesmentioning
confidence: 99%